2005
DOI: 10.1038/sj.bjc.6602544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cisplatin on olfactory function in cancer patients

Abstract: A prospective analysis of olfaction was performed in 21 patients receiving cisplatin. A reduction in olfactory function was noted in only one patient. Hearing impairment was documented in nine patients, none of whom had impaired sense of smell. We conclude that cisplatin has no major deleterious effect on olfactory function at doses which cause hearing impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…In accordance with our results, in both studies [11,12] odor identification of patients undergoing chemotherapy was hardly affected, whereas odor threshold score significantly decreased. These results were confirmed by other research investigating olfactory function of patients undergoing cisplatin containing chemotherapy protocols, that showed odor ID unaffected [7,13].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In accordance with our results, in both studies [11,12] odor identification of patients undergoing chemotherapy was hardly affected, whereas odor threshold score significantly decreased. These results were confirmed by other research investigating olfactory function of patients undergoing cisplatin containing chemotherapy protocols, that showed odor ID unaffected [7,13].…”
Section: Discussionsupporting
confidence: 83%
“…They could demonstrate a significant decrease in TDI score during the chemotherapy [8]. In addition, in a cohort of 87 cancer patients (breast cancer or gynecologic malignancies) undergoing various chemotherapy regimens (27% of those platinum containing) it could be demonstrated that olfactory function decreased significantly during chemotherapy but recovered almost completely after termination of the therapy [13]. These results were reaffirmed by a following study investigating 12 ovarian cancer patients receiving carboplatin containing chemotherapy [12].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Only a few objective studies have focused on olfactory changes during chemotherapy [6][7][8], particularly ovarian cancer patients as a separate group [6]. In the study of Ovesen et al [6], olfactory thresholds did not change in 6 ovarian cancer patients at re-evaluation after 2-3 months' chemotherapy.…”
Section: Introductionmentioning
confidence: 97%
“…7 Significantly decreased sense of smell was objectively shown in women with estrogen positive breast cancer. 1 Although subjective olfactory function impairment in oncologic patients has been mentioned in a considerable number of publications, the latter study, 1 the work of Ovesen et al 15 who evaluated changes in olfactory thresholds prior to and after treatment with several chemotherapeutic agents, and our previous study 16 are the only objective studies of olfaction in oncologic patients thus far.…”
Section: Discussionmentioning
confidence: 86%